W.P. Murray, City Attorney, The Municipal Code of Saint Paul: Comprising the Laws of the State of Minnesota Relating to the City of Saint Paul, and the Ordinances of the Common Council; Revised to December 1, 1884, pg. 39, no. 19 (1884) - (:unkn) unknown (General Publisher, 1884)
To provide for the receipt, storage, transportation, safe keeping and dealing and traffic in gun powder, gun cotton, petroleum, kerosene or other dangerous, explosive or inflammable oils or substances within said city, or within one mile of the corporate limits thereof, and to provide for the summary condemnation or destruction of any of said articles as may be kept, stored, dealt in, transported through or received in said city, contrary to such ordinance s said city may enact for the safety of life and property therein.]
--
Keywords: TRANSFER; MANUFACTURE & STORAGE OF GUNPOWDER